Efektivitas Implementasi Peraturan Wali Kota Padang Nomor 32 Tahun 2021 tentang Tata Cara Penguncian Ban, Penderekan, dan/atau Pemindahan Kendaraan Bermotor dalam Penertiban Parkir di Bahu Jalan oleh Dinas Perhubungan Kota Padang - Bima Fachwa; Hasbullah Malau (YASIN, 2026)
Illegal parking on road shoulders has become an urgent problem in urban areas because high levels of traffic and commercial activity encourage the use of road shoulders, which should function as spaces for vehicle movement. Although the Padang City Government has enacted Padang Mayor Regulation Number 32 of 2021 concerning Procedures for Wheel Clamping, Towing, and/or Relocating Motor Vehicles, empirical studies on the effectiveness of its implementation remain limited. This study aimed to analyze the effectiveness of implementing the regulation in controlling parking on road shoulders and to identify the factors affecting its implementation. The study employed a qualitative approach with a descriptive case study design involving 12 informants, consisting of officials from the Padang City Transportation Agency, field enforcement officers, residents, and business operators at four enforcement locations selected through purposive sampling. Data were collected through semi-structured interviews, direct observation, and document analysis and were subsequently analyzed using an interactive model through the stages of data condensation, data presentation, and conclusion drawing. Data validity was strengthened through source and method triangulation. The results showed that policy implementation had been procedurally effective, as indicated by the fulfillment of five effectiveness indicators, namely policy appropriateness, implementers, targets, environment, and process. Policy implementation was also supported by adequate communication, resources, disposition, and bureaucratic structure. However, enforcement outcomes were not yet optimal because parking violations continued to recur even though the number of vehicles towed decreased from 115 units in 2024 to 88 units in 2025. The main constraints included weak continuity of supervision after officers left the locations, a limited number of tow trucks, and insufficient alternative parking spaces. This study concluded that effective parking enforcement requires strengthened continuous field supervision, additional tow trucks, and the provision of adequate parking facilities. These findings contribute to the development of studies on local traffic policy implementation and provide practical recommendations for the Padang City Government to improve the sustainability and consistency of parking enforcement on road shoulders.